Connecting gasification with syngas fermentation: Comparison of the performance of lignin and beech wood. (15th April 2021) - Liakakou, E.T.; Infantes, A.; Neumann, A.; Vreugdenhil, B.J.
Abstract: The integration of gasification with syngas fermentation is still in an early stage of development, where many questions exist concerning the syngas quality required. The challenge is to define the gasification conditions that will provide a H2 :CO:CO2 ratio suitable for syngas fermentation, as well as to identify and remove the compounds that can inhibit the performance of the microorganisms. The right balance between the gasification conditions and a line up with minimal gas cleaning needs to be assessed to improve the economic feasibility of the process. In this work a first attempt to combine the two processes is presented, with the aim to provide an insight of the indirect gasification, the gas cleaning applied, the effect of the main impurities and the performance of syngas fermentation. A lignin rich feedstock was gasified with steam in an indirect gasifier, at TNO (Netherlands Organization for Applied Scientific Research). The gas, after removal of some components that could hinder the performance of the fermentation (tar compounds, BTX, unsaturated hydrocarbons and sulphur compounds), consisted of CO, H2, CO2, CH4, C2 H6 and traces of other hydrocarbons. The influence of the obtained syngas quality and composition was evaluated in the fermentation process using Clostridium ljungdahlii, at KIT (Karlsruhe Institute of Technology). For comparison, product gas from beech wood gasification was also evaluated in the fermentation process under the same conditions.